2015
DOI: 10.1371/journal.pone.0137850
|View full text |Cite
|
Sign up to set email alerts
|

Convex-Envelope Based Automated Quantitative Approach to Multi-Voxel 1H-MRS Applied to Brain Tumor Analysis

Abstract: BackgroundMagnetic Resonance Spectroscopy (MRS) can measure in vivo brain tissue metabolism that exhibits unique biochemical characteristics in brain tumors. For clinical application, an efficient and versatile quantification method of MRS would be an important tool for medical research, particularly for exploring the scientific problem of tumor monitoring. The objective of our study is to propose an automated MRS quantitative approach and assess the feasibility of this approach for glioma grading, prognosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The Wartburg effect shows that cancer is a metabolic disease and that many tumor cells produce energy via glycolysis during cell proliferation [ 25 – 27 ]. Many researchers have attempted to use metabolites to aid in the monitoring of tumor cell treatment in the central nervous system with some success [ 15 , 16 ]. Glycolysis provides energy for tumor cells and produces lactate [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Wartburg effect shows that cancer is a metabolic disease and that many tumor cells produce energy via glycolysis during cell proliferation [ 25 – 27 ]. Many researchers have attempted to use metabolites to aid in the monitoring of tumor cell treatment in the central nervous system with some success [ 15 , 16 ]. Glycolysis provides energy for tumor cells and produces lactate [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glycolysis provides energy for tumor cells and produces lactate [ 17 ]. Changes in lactate levels are closely connected with the proliferation and apoptosis rates of glioma cell lines [ 9 , 15 ]. Creatineis a stable molecule in nerve cells and nervous system tumors, and is employed here as an internal reference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can provide information on the neuronal integrity and on the levels of neurotransmitters including N -acetylaspartate (NAA), a neuronal marker, choline (Cho), which is involved in the synthesis and degradation of cell membranes, creatine (Cr), which reflects the energetic activity in the cells, lipid (Lip), a product of membrane phospholipids and necrotic debris, and lactate (Lac), which correlates with anaerobic glycolysis. In many studies, 1 H-MRS has been shown to determine the tumor type and grade (Dou et al, 2015). 1 H-MRS adds relevant diagnostic value exceeding that obtained from structural MR imaging alone.…”
Section: Introductionmentioning
confidence: 99%